Endometriosis: Pathogenesis, diagnosis, treatment and the role of gut microbiota - Senat, Hanna; Grabowska, Patrycja; Senat, Aleksandra; Bolla, Patrycja; Madej, Aleksandra; Marczyńska, Zuzanna; Libracka, Karolina (Journal of Education, Health and Sport, 2024)
Endometriosis is a common disease. It affects 5-10% of women of reproductive age worldwide. However, despite the prevalence, diagnosis is typically delayed by years, misdiagnosis is common, and effective treatment takes years to achieve. Determining the mechanisms involved in its pathogenesis is vital, not only to pave the way for early identification, but also for disease management and development of less invasive but successful treatment strategies. Three main typed of endometriosis have been described in literature: peritoneal, ovarian and deep infiltrative. This is mainly due to the most common locations of ectopis endometrium. .Determining the precise pathogenesis of endometriosis has proved challenging and controversial for gynecologists, endocrinologists and researchers, but recent studies have focused on finding answers. This disease is often asymptomatic and diagnosed incidentally during various surgical interventions or follow-up gynecological examinations. Epidemiological research reports that women with this disease are more vulnerable to ovarian and breast cancer, asthma, skin cancer suhc as melanoma, cardiovascular disease and rheumatoid arthritis. The connection of the gut microbiota and endometriosis is nowadays higly suspected to exist. Scientists are focused on the influence of the microbiome on estrogens, estrogens-dependent disorders, immune system and inflammation. It is strongly velieved that correction of the gut microbiota with antibiotica, probiotics, or fecal bacterial transplantation sie a hopeful method for improving the clinical management of endometriosis.